Silver nanoparticles from insect wing extract: Biosynthesis and evaluation for antioxidant and antimicrobial potential. - Parameshwar Jakinala; Nageshwar Lingampally; Bee Hameeda; R Z Sayyed; Yahya Khan M; Elsayed Ahmed Elsayed; Hesham El Enshasy (PLoS ONE, 2021)
Silver nanoparticles (AgNPs) are among the most widely synthesized and used nanoparticles (NPs). AgNPs have been traditionally synthesized from plant extracts, cobwebs, microorganisms, etc. However, their synthesis from wing extracts of common insect; Mang mao which is abundantly available in most of the Asian countries has not been explored yet. We report the synthesis of AgNPs from M. mao wings extract and its antioxidant and antimicrobial activity. The synthesized AgNPs were spherical, 40-60 nm in size and revealed strong absorption plasmon band around at 430 nm. Highly crystalline nature of these particles as determined by Energy-dispersive X-ray analysis and X-ray diffraction further confirmed the presence of AgNPs. Hydrodynamic size and zeta potential of AgNPs were observed to be 43.9 nm and -7.12 mV, respectively. Fourier-transform infrared spectroscopy analysis revealed the presence of characteristic amide proteins and aromatic functional groups. Thin-layer chromatography (TLC) and Gas chromatography-mass spectroscopy (GC-MS) analysis revealed the presence of fatty acids in the wings extract that may be responsible for biosynthesis and stabilization of AgNPs. Further, SDS-PAGE of the insect wing extract protein showed the molecular weight of 49 kDa. M. mao silver nanoparticles (MMAgNPs) exhibit strong antioxidant, broad-range antibacterial and antifungal activities, (66.8 to 87.0%), broad-range antibacterial and antifungal activities was found with maximum zone of inhibition against Staphylococcus aureus MTCC 96 (35±0.4 mm) and Fusarium oxysporum f. sp. ricini (86.6±0.4) which signifies their biomedical and agricultural potential.